A type of Rabinowitz Theorem for compact operators on a strip and an application to a quasilinear problem - Ramos, Vinicius Kobayashi (2021)
Dissertação (mestrado)—Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Matemática, 2021.